THE EXTENT OF IMPLEMENTING CRISIS MANAGEMENT IN MINISTRIES IN THE REPUBLIC OF YEMEN - Shaker M. Al-Kahtani, Mohammed M. Al Nadesh, Mustafa Q. Ghaleb, Mansour. M. Almasagedi, Muntaser A. Almaamari (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The purpose of the paper: To identify the administrative behavior (preparations) in the Ministry of Technical Education and Vocational Training in the Republic of Yemen in facing crises before, during and after their occurrence. The objective of the research: This paper tries to identify the administrative behavior (preparations) in the Ministry of Technical Education and Vocational Training in the Republic of Yemen towards crises before, during and after their occurrence from the viewpoint of officials and managers of the Ministry of Technical Education and Vocational Training in addition to the family evaluation of ministry officials for the process of dealing with crises before During and after their occurrence and knowing the causes of crises from the point of view of officials and directors of departments in the ministry, the reality of crisis management in its various stages and how to prepare for it, the researcher used the questionnaire and it was designed based on the theoretical literature for the study and after conducting a series of meetings with officials and directors of departments in the ministry, while the second part of the questionnaire included On questions and (38) questions, the researcher used statistical treatment. The Statistical Package for the Social Sciences Program includes Reference Analytics (SPSS). Society and Study Sample The study population is the Ministry of Technical Education and Vocational Training in the Republic of Yemen. The respondents are officials and directors of the sample sections and all the employees of the Ministry's General Bureau. The study enabled the researcher to study the results of administrative behavior (preparations) in the Ministry of Technical Education and Vocational Training in the Republic of Yemen in facing crises before, during and after their occurrence. The study concluded with a set of results, the most important of which is that the ministry does not It has the ability and is not prepared to face crises before, during and after their occurrence for a number of reasons, including the war in Yemen for six reasons. Reasons. Years. In addition to the lack of an adequate budget for the ministry to face the crises as a result of the destruction of the national and national economy of Yemen. Also, the Ministry did not open up to the external environment and benefit from it.